REPORT OF THE COMMITTEE ON COURSES AND CURRICULA. - Barnes, B. L.; Christiansen, Irving K.; Lawrence, Charles; Myers, John H.; Rinder, George G.; Wolosin, Harold J.; Fertig, Paul E. (The Accounting Review, 1963)
Abstract The task assigned the 1962 Courses and Curricula Committee of the American Accounting Association was "to develop criteria for selecting the content and quality of collegiate accounting educational materials to provide adequate instruction in the body of knowledge that is accounting." The 1961 Committee, which was kept intact for a second year, decided that this task was possible after it discarded other more limited objectives because they involved too many restrictive assumptions to produce useful conclusions. To reduce its task to manageable proportions, the Committee decided to exclude so-called "service" courses, in which accounting is taught primarily to students who are preparing for careers other than accounting careers. For example, the first course in accounting is not considered, since it is offered primarily for those students who do not plan to go on in accounting. As a result, these recommendations apply only to schools which have as one of their objectives educating college students who intend to enter the business world as accountants in industrial, governmental, or public accounting organizations.